The Interactive Effect of Pruning Level and Irrigation Strategy on Grape Berry Ripening and Composition in Vitis vinifera L. cv. Shiraz - Bindon, K.A.; Dry, P.R.; Loveys, B.R. (South African Journal of Enology and Viticulture, 2016)
A partial rootzone drying (PRD) irrigation technique (0.5 ML/ha) was compared with a standard irrigation treatment (1 ML/ha) at three different pruning levels of 30, 60 and 120 nodes per grapevine in Vitis vinifera L. cv Shiraz. Berry size was found to decrease as node number per grapevine increased, but was not significantly altered by the PRD treatment. The influence of these treatments on the accumulation of total soluble solids per berry was investigated during berry ripening and was shown to be reduced at higher node number (120 nodes). There was no effect of PRD on the accumulation of total soluble solids. Juice titratable acidity and the concentration (per g) and content (per berry) of grape anthocyanins and phenolics were compared between treatments at harvest. In one season of the study, juice titratable acidity, anthocyanin and phenolic concentration was unaltered by the PRD treatment. In a further season, juice titratable acidity was decreased in response to the PRD treatment and was associated with increases in grape anthocyanin and phenolic concentration in response to PRD. Where there was a small increase in anthocyanin concentration in response to PRD, this was found to be independent of berry size. In addition, linear regression analysis showed a poor relationship between berry size and anthocyanin concentration, but a significant relationship was found between berry size and anthocyanins per berry.